Abnormal Uterine Bleeding in Adolescent - Kms Yusuf Effendi; Rizani Amran; Iskandar Zulqarnain; Heriyadi Manan; Adnan Abadi; Fatimah Usman; Awan Nurtjahyo; Cindy Kesty; Siti Chodijah; Selly Rizany (HM Publisher, 2022)
Abnormal uterine bleeding (AUB) is defined as the abnormal bleeding from the uterine corpus in term of duration, volume, frequency and/or regularity. This condition occurs in 37% of adolescents and may affect the quality of life and increased hospitalization. Etiology is divided into structural and non-structural causes, known as PALM-COEIN. The most common etiology in adolescents is anovulatory menstruation due to immature hypothalamus-hypophysis axis. Diagnostic evaluation should include investigation in the etiology of AUB, anemia signs, and hemodynamic status. Treatment of AUB consists of hormonal and non-hormonal therapy. Therapy in adolescent is given based on the severity of bleeding, grading of anemia, and hemodynamic stability. Follow-up is required after therapy. Understanding AUB in adolescents can help clinicians deliver appropriate and comprehensive treatment. This review was aimed to explain about definition, epidemiology, etiology, pathophysiology, diagnosis, and treatment of abnormal uterine bleeding in adolescent.